Baltų ir slavų kalbų vardažodžių daryba (senosios bendrybės ir skirtybės) - Ambrazas, Saulius (Baltistica, 1992)
WORD FORMATION OF NOUNS IN BALTIC AND SLAVIC (old common traits and differences)The article deals with the problem of relations of Baltic and Slavic languages on the base of word formation of nouns. Some archaic features of Slavic word formation in comparison with Baltic one are distinguished:1) nomina agentis with old Indo-European suffix *-tel- were left whale in Slavic, but they were completly pushed out by the corresponding derivatives with new suffixes   *-tāi̯o- (